2017
DOI: 10.1002/2017gl075092
|View full text |Cite
|
Sign up to set email alerts
|

Charge Proportional and Weakly Mass‐Dependent Acceleration of Different Ion Species in the Earth's Magnetotail

Abstract: Energetic particles with energies from tens of keV to a few hundred keV are frequently observed in the Earth's magnetotail. Here we study, by means of a test particle numerical simulation, the acceleration of different ion species (H+, He+, He++, and On+ with n = 1–6) in the presence of transient electromagnetic perturbations. All the considered ions develop power law tails at high energies, except for O+ ions. This is strongly correlated to the time that the particle spends in the current sheet. Ion accelerat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
5
12
0
Order By: Relevance
“…Journal of Geophysical Research: Space Physics dependent energization and high temporal correlation do not necessarily imply adiabaticity (Catapano et al, 2017;Ukhorskiy et al, 2018). The results from the study presented here cannot determine the dominant mechanism of ion energization in the tail, other than to show that it roughly orders the energization according to E/q.…”
Section: 1029/2020ja028144mentioning
confidence: 55%
See 2 more Smart Citations
“…Journal of Geophysical Research: Space Physics dependent energization and high temporal correlation do not necessarily imply adiabaticity (Catapano et al, 2017;Ukhorskiy et al, 2018). The results from the study presented here cannot determine the dominant mechanism of ion energization in the tail, other than to show that it roughly orders the energization according to E/q.…”
Section: 1029/2020ja028144mentioning
confidence: 55%
“…For example, as noted earlier, ion drift across an ideal flow channel with an enhanced electric field will adiabatically produce charge‐dependent energization and E / q‐ dependent drift trajectories (Mitchell et al, 2018). Test particle simulations of ion interactions with stochastic electromagnetic fluctuations, like those accompanying dipolarization fronts in the magnetotail, have shown primarily charge‐dependent energization with only a small mass dependency (Catapano et al, 2017). Additionally, test particle MHD simulations have suggested that magnetic islands can form within dipolarization fronts and lead to circumferential gradient drifts around the island and nonadiabatic charge‐state‐dependent energization (Ukhorskiy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high E y due to relatively high cross‐tail potential (DiBraccio et al, ; Jasinski et al, ; Slavin et al, , ) would result in strong cross‐tail acceleration for protons at Mercury. The other possible candidate is wave‐particle interactions (e.g., Catapano et al, ; Hasegawa et al, ; Shizgal, ). For the case in Figure , we do observe intense plasma waves with frequencies around the proton gyrofrequency, especially after the dipolarization in the wavelet spectrum of MAG data (see supporting information).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…First, the finite ion gyroradius effect (which is even more important for heavy ions) results in violation of the adiabaticity in ion motions (Artemyev et al, 2015) and thus can provide mass/charge dependence (Greco et al, 2015). Second, broadband electromagnetic turbulence accompanying the dipolarization fronts (Chaston et al, 2012; Ergun et al, 2015; Kronberg et al, 2019) can locally demagnetize ions and violate adiabatic approximation (Catapano et al, 2017; Greco et al, 2017). Third, combination of ion drifts along the front boundary and gradient drifts in the ambient inhomogeneous field destroys ion trapping and can provide charge‐dependent acceleration (Ukhorskiy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%